Knowledge, attitudes, and practices regarding antimicrobial resistance and antimicrobial stewardship among healthcare workers in outpatient medical centers in Kenya: a qualitative study - Mary W. Kaniu; Wahu R. Gitaka; Rupali Jain; Ann N. Munyare; Rodney D. Adam; Aliza Monroe-Wise (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract